Inhibition of miR-128-3p by Tongxinluo Protects Human Cardiomyocytes from Ischemia/reperfusion Injury via Upregulation of p70s6k1/p-p70s6k1 - Chen, Gui-hao; Xu, Chuan-sheng; Zhang, Jie; Li, Qing; Cui, He-he; Li, Xiang-dong; Chang, Li-ping; Tang, Rui-jie; Xu, Jun-yan; Tian, Xia-qiu; Huang, Pei-sen; Xu, Jun; et al. (Frontiers in Pharmacology, 2017)
Background and aims: Tongxinluo (TXL) is a multifunctional traditional Chinese medicine that has been widely used to treat cardiovascular and cerebrovascular diseases. However, no studies have explored whether TXL can protect human cardiomyocytes (HCMs) from ischemia/reperfusion (I/R) injury. Reperfusion Injury Salvage Kinase (RISK) pathway activation was previously demonstrated to protect the hearts against I/R injury and it is generally activated via Akt or (and) Erk 1/2, and their common downstream protein, ribosomal protein S6 kinase (p70s6k). In addition, prior studies proved that TXL treatment of cells promoted secretion of VEGF, which could be stimulated by the increased phosphorylation of one p70s6k subtype, p70s6k1. Consequently, we hypothesized TXL could protect HCMs from I/R injury by activating p70s6k1 and investigated the underlying mechanism. Methods and results: HCMs were exposed to hypoxia (18 h) and reoxygenation (2 h) (H/R), with or without TXL pretreatment. H/R reduced mitochondrial membrane potential, increased bax/bcl-2 ratios and cytochrome C levels and induced HCM apoptosis. TXL preconditioning reversed these H/R-induced changes in a dose-dependent manner and was most effective at 400 µg/mL. The anti-apoptotic effect of TXL was abrogated by rapamycin, an inhibitor of p70s6k. However, inhibitors of Erk1/2 (U0126) or Akt (LY294002) failed to inhibit the protective effect of TXL. TXL increased p70s6k1 expression and, thus, enhanced its phosphorylation. Furthermore, transfection of cardiomyocytes with siRNA to p70s6k1 abolished the protective effects of TXL. Among the micro-RNAs (miR-145-5p, miR-128-3p and miR-497-5p) previously reported to target p70s6k1, TXL downregulated miR-128-3p in HCMs during H/R, but had no effects on miR-145-5p and miR-497-5p. An in vivo study confirmed the role of the p70s6k1 pathway in the infarct-sparing effect of TXL, demonstrating that TXL decreased miR-128-3p levels in the rat myocardium during I/R. Transfection of HCMs with a hsa-miR-128-3p mimic eliminated the protective effects of TXL. Conclusions: The miR-128-3p/p70s6k1 signaling pathway is involved in protection by TXL against HCM apoptosis during H/R. Overexpression of p70s6k1 is, therefore, a potential new strategy for alleviating myocardial reperfusion injury.